Spotlight on Impactful Research: Universal Screening for Alcohol Misuse in Acute Admissions Is Feasible and Identifies Patients at High Risk for Liver Disease. Issue 3 (2nd October 2018) - Mellinger, Jessica L.
Abstract : Watch a video presentation of this article